Virtual hospital-level care—feasibility, acceptability, safety and impact of a pilot Hospital-In-The-Home model for COVID-19 infection - Lawrence, J.; Truong, D.; Dao, A.; Bryant, P. A. (Frontiers in Digital Health, 2023)
Hospital-in-the-Home (HITH) delivers hospital level care to patients in their homes. We designed and implemented a virtual model of care for children with COVID-19 in response to rising patient numbers, infection risk and pressures on equipment. In contrast to other models for COVID-19 infection in Australia, our HITH service catered only for children who were unwell enough to require hospitalisation (ie bed-replacement). Aims: To measure feasibility, acceptability, safety and impact of a virtual model of care for managing children with COVID-19 infection requiring hospital-level care. Methods: Retrospective study of a new virtual model of care for all children admitted to the Royal Children’s HITH service with COVID-19 infection between 7th October 2021 and 28th April 2022. The model consisted of video consultations, remote oximetry, symptom tracking, portal messaging and 24-hour teleconsultation support. Patients were eligible if they met hospital-level severity without requiring intravenous fluids, oxygen or intensive care. Online surveys were distributed to staff and consumers. Results: 331 patients were managed through the virtual HITH program with a mean length of stay of 3.5 days. Of these, 331 (100%) engaged in video consultations, 192 (58%) engaged in the patient portal and completed the symptom tracker a total of 634 times and sent a total of 783 messages. Consumer satisfaction (n=31) was high (4.7/5) with the most useful aspect of the model considered video consultation. Clinician satisfaction (n=9) was also high with a net promoter score of 8.9. There were no adverse events at home. Eight children (2.4%) represented to hospital, 7 (2.1%) of whom were readmitted. The impact is represented by a total of 1312 hospital bed-days saved in the seven-month period (2249 bed-days per year). In addition, 1480 home visits (travel time/ protective equipment/ infection risk) were avoided. Conclusion: A virtual HITH program for COVID-19 in children is feasible, acceptable and safe and has a substantial impact on bed-days saved and nursing travel time. The implications for management of other acute respiratory viral illnesses that contribute to hospital bed pressure during winter months is immense. Virtual HITH is likely to be a key enabler of a sustainable healthcare system.